Investigation of the relationship between morphology and permeability for open-cell foams using virtual materials testing. (5th June 2018) - Westhoff, Daniel; Skibinski, Jakub; Šedivý, Ondřej; Wysocki, Bartlomiej; Wejrzanowski, Tomasz; Schmidt, Volker
Abstract: The effect of the morphology of open-cell foam structures on their functional properties is investigated. A stochastic microstructure model is used to generate representative 3D open-cell foam structures, where morphological properties are systematically varied. Subsequently, permeability of these virtual, but realistic microstructures is determined using the finite volume method. This procedure, which is called virtual materials testing, has recently been employed to investigate the effect of the variation of cell sizes on permeability. In the present paper, we introduce a stochastic microstructure model that can be used to generate structures with varying distribution of (open) face sizes between cells. It turns out that this characteristic strongly influences the so-called constrictivity, a measure for bottleneck effects, which, in turn, has a strong impact on the resulting permeability. Moreover, we show how the virtual materials testing approach can be applied to derive empirical formulas between descriptors of 3D morphology and functionality. Additionally, an experimental validation of the simulation results is performed by printing three of the virtual structures using selective laser melting and subsequent experimental measurement of pressure drop, which allows calculation of the permeability using Darcy's law. Graphical Abstract: Highlights: A stochastic 3D microstructure model is used to generate open-cell foam structures with varying distribution of face sizes. The coefficient of variation of face sizes strongly influences constrictivity, a measure for bottleneck effects Permeability of the virtual, but realistic microstructures with different values of constrictivity is simulated. An experimental validation is performed by 3D printing of some structures and experimental measurement of pressure drop. A linear relationship between constrictivity and permeability is found, where other structural properties are kept fixed.